Studi Sifat Mekanik Komposit Isotropik Al/SiO2 Hasil Fabrikasi dengan Metalurgi Serbuk: Hanafi, Munasir, Mochamad Zainuri - Hanafi, Hanafi; Munasir, Munasir; Mochamad Zainuri, Mochamad Zainuri (Jurnal Fisika dan Aplikasinya, 2025)
Composites of Al/SiO2 have been fabricated through powder metallurgy method using aluminium as matrix and combined with nano silica (SiO2). SiO2 was obtained from the synthesis of sand of Bancar Tuban through copresipitation method. Fabrication of composites was performed by powder metallurgy method by the wet mixing method, by using butanol as solution. The sample was sintered at a temperature of 500C for 2 hours in a vacuum furnace. The samples were analyzed and tested to determine its properties, as density, porosity, and tested by XRD, SEM-EDX and pressure test. The results showed that based on the XRD analysis was obtained composite Al/SiO2 at x= 0% to 30% with a crystalline phase of Al and Al2O3 and SiO2 slightly indicated by a low peak. Increased of the volume fraction of SiO2 on composite was tended to decrease of density and increase porosity. The results of mechanical tests was show that yield strength (YS), compressive strength (CS), elastic modulus (EM), hardness tends to decrease with increasing volume fraction of the composite of SiO2. Value YS, CS, EM and hardness of materials has the highest value when the volume fraction of SiO2 in the composite is 5%.